Experimental and numerical studies of natural convection from horizontal concrete cylinder heated with a cylindrical heat source - Demir, Hakan (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Natural convection heat transfer from horizontal concrete cylinder heated with cylindrical heat source was investigated experimentally and numerically. Bare cylinder having a diameter of 9.45 mm was buried in a cylindrical concrete cylinder and thermocouples located outside the copper tube and inside and outside of the concrete cylinder in axial, radial and angular directions. Experiments are conducted at 20 degrees C and 30 degrees C ambient temperatures in a conditioned room. Copper cylinder surface temperatures varied between 30-50 degrees C and 40-50 degrees C for 20 degrees C and 30 degrees C ambient temperatures respectively. In a numerical study, the measured temperatures in the experimental study were used for boundary conditions. Experimental and numerical results were compared and heat transfer enhancement was seen for concrete cylinder. Also the effect of the decrease in the temperature of the copper tube surface was investigated on an ideal Carnot refrigerator. It is found that the enhancement in the coefficient of performance of a Carnot refrigerator is about 35%. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Heat transfer; Numerical analysis; Cylindrical surface; Coefficient of performance; EQUATIONS; LAMINAR; SURFACE; Thermodynamics; Mechanics